Glycemic index and glycemic load: Challenges and benefits of clinical applicability - Passos, Taciana Uchôa; Passos, Tatiana Uchôa; Sampaio, Rafaella Maria Monteiro; Brito, Fernando César Rodrigues (Seven Editora, 2023)
More than 40 years ago, studies about the glycemic index (GI) and glycemic load (GL) began. However, nowadays there is still no consensus regarding dietary prescription based on these indices in the main national and international guidelines. Paradoxically, there is a growing number of research studies pointing to the benefits of diets with low GI and GL. The literature shows that there are still limitations regarding determination protocols, gaps regarding regional foods and the GI's focus on the glycemic response two hours after ingestion. On the other hand, the interest of the scientific community is growing and further studies on the effect of different carbohydrate sources on blood glucose are quite attractive. Evidence of the harm caused by blood glucose and insulin spikes in the development of chronic non-communicable diseases is also an important justification for the emergence of new investigations, despite the limitations highlighted by health guidelines. DOI:https://doi.org/10.56238/sevened2023.004-027